Modified polytetrafluoroethylene sealing ring and preparation method thereof
By adding specific raw materials and process to the polytetrafluoroethylene sealing ring, a sealing ring with excellent aging resistance and wear resistance was prepared, which solved the problem of degradation of the aging performance of the polytetrafluoroethylene sealing ring and significantly extended its service life.
Patent Information
- Application Number
- CN202411759616.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-14
AI Technical Summary
The performance of the polytetrafluoroethylene sealing ring deteriorates during the aging process, has poor mechanical properties and low hardness, which affects its service life.
By adding pretreated glass fiber, modified graphite, rubber-plastic alloy rubber, polystyrene, wear-resistant agent, reinforcement and silane coupling agent to the polytetrafluoroethylene sealing ring, sealing ring with excellent aging resistance and wear resistance is prepared by mixing, melting, cold press forming and calcining processes.
It significantly improves the aging resistance and wear resistance of the PTFE sealing ring, extends its service life, and improves its performance stability in high temperature environments.
Smart Images

Figure BDA0005167276400000081 
Figure BDA0005167276400000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polytetrafluoroethylene sealing rings and relates to a modified polytetrafluoroethylene sealing ring and a preparation method thereof. Background Art
[0002] Polytetrafluoroethylene resin is a high molecular polymer made by polymerizing tetrafluoroethylene as a monomer. It is white waxy, translucent, heat-resistant and cold-resistant, and can be used for a long time at -180 to 260°C. Polytetrafluoroethylene sealing rings are made of polytetrafluoroethylene resin, which is cold-pressed and sintered with a mold. It has excellent corrosion resistance, good self-lubrication and non-stick properties.
[0003] PTFE seals have good dimensional stability, electrical insulation, chemical inertness and high temperature adaptability. However, PTFE seals are not resistant to strong oxidants, have poor mechanical properties and low hardness, and their performance and life are affected by aging.
[0004] Therefore, it is necessary to develop a polytetrafluoroethylene sealing ring with good hardness and aging resistance. Summary of the invention
[0005] The object of the present invention is to provide a polytetrafluoroethylene sealing ring and a preparation method thereof. The prepared polytetrafluoroethylene sealing ring has excellent aging resistance and wear resistance.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A modified polytetrafluoroethylene sealing ring comprises the following raw materials in parts by weight: 70-85 parts of polytetrafluoroethylene, 10-15 parts of pretreated glass fiber, 15-25 parts of rubber-plastic alloy rubber, 5-9 parts of polystyrene, 3-5 parts of modified graphite, 3-5 parts of wear-resistant agent, 5-10 parts of reinforcing agent, and 3-5 parts of silane coupling agent;
[0008] The specific preparation process of the pretreated glass fiber is as follows:
[0009] The glass fiber is baked at 350-400° C. for 2-3 hours to obtain pretreated glass fiber.
[0010] As a preferred technical solution of the present invention, the preparation process of the modified graphite is as follows:
[0011] First, the graphite is calcined at high temperature and then naturally cooled to room temperature to obtain solid A, the solid A with a mass ratio of 1: (1.5-3) and the intercalation agent solution are mixed evenly, impregnated for 2-3 hours, filtered and washed with water to obtain solid B; the solid B with a mass ratio of 1: (1-2) and the anti-aging solution are mixed evenly, impregnated for 2-4 hours, and dried at 95-105° C. to obtain the modified graphite;
[0012] The anti-aging solution comprises the following components in parts by weight: 10 to 20 parts of sodium tetraborate, 10 to 15 parts of copper chloride, 5 to 10 parts of chlorogenic acid, 5 to 10 parts of ethanol and 40 to 65 parts of water.
[0013] As a preferred technical solution of the present invention, the wear-resistant agent is one or more of carbon powder, carbon fiber, copper powder and molybdenum disulfide.
[0014] As a preferred technical solution of the present invention, the silane coupling agent is one or more of KH550, KH560 and KH570.
[0015] As a preferred technical solution of the present invention, the reinforcing agent is aramid fiber and cerium oxide in a mass ratio of (4-8): (2-4).
[0016] As a preferred technical solution of the present invention, the intercalant solution comprises the following components by weight: 10 to 15 parts of sulfuric acid, 1 to 3 parts of sodium dodecyl sulfate, 4 to 6 parts of phosphoric acid
[0017] As a preferred technical solution of the present invention, the temperature of the graphite during high-temperature calcination is 300-360° C. and the time is 2-3 hours.
[0018] A method for preparing a modified polytetrafluoroethylene sealing ring includes the following preparation processes:
[0019] S1, adding polytetrafluoroethylene, pretreated glass fiber, rubber-plastic alloy rubber, polystyrene, modified graphite, wear-resistant agent, and reinforcing agent into a pulverizer in proportion and mixing and pulverizing to obtain a mixture A;
[0020] S2, after passing the mixture A through a 200-mesh sieve, put it into a mixing device, add a silane coupling agent and continue stirring, the speed of the stirring rod of the mixing device is 900-1300 r / min, and after stirring for 15-25 minutes, a mixture B is obtained;
[0021] S3, heating the mixed material B to completely melt and then cold pressing to obtain a raw material blank;
[0022] S4, calcining the raw material blank at 360-400° C. for 5-7 hours, cooling it to 250-280° C. and keeping it at that temperature for 1-2 hours, and then keeping it at a pressure of 8-14 MPa for 20-30 minutes to obtain the modified polytetrafluoroethylene sealing ring.
[0023] As a preferred technical solution of the present invention, in step S3, the heating temperature is 200-230°C.
[0024] As a preferred technical solution of the present invention, in step S3, during the cold pressing process, the pressure is 40-55 MPa and the time is 25-35 min.
[0025] In the present invention, the glass fiber is firstly subjected to a calcination treatment, so that the surface properties of the calcined glass fiber are changed. The calcination process makes the internal structure of the glass fiber more stable, and optimizes the overall structure of the glass fiber.
[0026] Graphite is roasted to remove volatile components and impurities therein, thereby improving the purity and overall performance of the graphite. Graphite is placed in an intercalation agent solution for treatment, and the intercalation agent can be inserted between the layered structures of the graphite. In the present invention, sulfuric acid, sodium dodecyl sulfate and phosphoric acid are mixed to obtain an intercalation agent solution, wherein sodium dodecyl sulfate is an excellent anionic surfactant that can effectively enter the interlayer of the graphite layered material, increase the interlayer spacing, and achieve a good intercalation effect. At the same time, sulfuric acid and phosphoric acid in the intercalation agent can promote the intercalation process and improve the reaction efficiency. After the intercalation is completed, the intercalation agent that has not been inserted into the graphite is removed by filtering and washing.
[0027] Chlorogenic acid and cupric chloride in the anti-aging solution have good antioxidant properties. The polyphenol structure contained in chlorogenic acid has strong antioxidant properties, and cupric chloride has the ability to scavenge free radicals. The buffering effect of sodium tetraborate increases the stability of the anti-aging solution. By immersing graphite in the anti-aging agent solution, the anti-aging property of graphite is improved, thereby reducing the occurrence of oxidation reactions and improving the anti-aging property of graphite.
[0028] Aramid fiber and cerium oxide are mixed as reinforcing agents. Aramid fiber has excellent high temperature resistance. When mixed with cerium oxide, it can further enhance the heat resistance of polytetrafluoroethylene and improve its anti-aging performance in high temperature environments. In addition, the high strength and toughness of aramid fiber can significantly improve the mechanical properties of polytetrafluoroethylene, such as wear resistance, thereby increasing the durability of polytetrafluoroethylene materials.
[0029] Rubber-plastic alloy rubber combines the advantages of rubber and plastic, and has excellent comprehensive properties such as wear resistance, corrosion resistance, and high elasticity. Adding rubber-plastic alloy rubber to the polytetrafluoroethylene-based material helps to improve the overall wear resistance of polytetrafluoroethylene. At the same time, polystyrene can fill the structural pores of polytetrafluoroethylene, thereby increasing the hardness and improving the overall mechanical properties of polytetrafluoroethylene materials.
[0030] Beneficial effects of the present invention:
[0031] The invention uses polytetrafluoroethylene as a base material, adds rubber-plastic alloy rubber and polystyrene to improve the mechanical properties of the material, and adds modified graphite that has been subjected to anti-aging treatment and modified glass fiber, combined with other raw materials, through mixing, melting, cold pressing and baking to prepare a polytetrafluoroethylene sealing ring with excellent anti-aging and wear resistance. DETAILED DESCRIPTION
[0032] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0033] The raw materials used in the following examples and comparative examples are as follows:
[0034] Polytetrafluoroethylene: purchased from Hefei Qihong Polymer Materials Co., Ltd., model F230;
[0035] Rubber-plastic alloy rubber: purchased from Saikede Rubber & Plastic, model: 5075D;
[0036] KH550: purchased from Tesco Chemical (Hubei) Co., Ltd.;
[0037] Glass fiber: purchased from Hubei Qifei Pharmaceutical Chemical Co., Ltd., product number: QF6055;
[0038] Sodium tetraborate: purchased from Hubei Yongkuo Technology Co., Ltd.;
[0039] Cupric chloride: purchased from Sichuan South China Inorganic Salt Co., Ltd.
[0040] Chlorogenic acid: purchased from Zhangjiajie Jiurui Biotechnology Co., Ltd., purity: 98%;
[0041] Phosphoric acid: purchased from Jinan Shanhai Chemical Technology Co., Ltd., purity: 85%;
[0042] Sodium dodecyl sulfate: purchased from Tesco Chemical (Hubei) Co., Ltd., product number: kns20220677;
[0043] Graphite: purchased from Yumu (Ningbo) New Materials Co., Ltd., product number: ASCCC;
[0044] Polystyrene: purchased from Tesco Chemical (Hubei) Co., Ltd., product number: tsk202302151621;
[0045] Aramid fiber: purchased from Jiangsu Runfeng Synthetic Technology Co., Ltd.;
[0046] Cerium oxide: purchased from Shanghai Jiader Chemical Technology Co., Ltd.
[0047] Example 1
[0048] Preparation of pretreated glass fiber:
[0049] The glass fiber was baked at 350°C for 2 hours to obtain pretreated glass fiber.
[0050] Preparation of modified graphite:
[0051] The anti-aging solution includes the following components in parts by weight: 10 parts of sodium tetraborate, 10 parts of copper chloride, 5 parts of chlorogenic acid, 5 parts of ethanol and 40 parts of water;
[0052] First, the graphite is calcined at 300°C for 2 hours and then naturally cooled to room temperature to obtain solid A. The solid A with a mass ratio of 1:1.5 is mixed evenly with an intercalation agent solution, impregnated for 2 hours, filtered and washed with water to obtain solid B. The solid B with a mass ratio of 1:1 is mixed evenly with an anti-aging solution, impregnated for 2 hours, and dried at 95°C to obtain the modified graphite.
[0053] Preparation of modified polytetrafluoroethylene sealing ring:
[0054] The intercalant solution includes the following components in parts by weight: 10 parts of sulfuric acid, 1 part of sodium dodecyl sulfate, and 4 parts of phosphoric acid;
[0055] S1. According to weight, 70 parts of polytetrafluoroethylene, 10 parts of pretreated glass fiber, 15 parts of rubber-plastic alloy rubber, 5 parts of polystyrene, 3 parts of modified graphite, 3 parts of carbon powder, and 5 parts of reinforcing agent are added into a pulverizer for mixing and pulverizing to obtain a mixture A, wherein the reinforcing agent is aramid fiber and cerium oxide in a mass ratio of 4:2;
[0056] S2, after passing the mixture A through a 200-mesh sieve, put it into a mixing device, and then add 3 parts of KH550 and continue stirring. The speed of the stirring rod of the mixing device is 900r / min. After stirring for 15 minutes, the mixture B is obtained;
[0057] S3, heating the mixed material B to 200°C, and after it is completely melted, cold pressing is performed at a pressure of 40 MPa to obtain a raw material blank after 25 minutes;
[0058] S4, calcining the raw material blank at 360° C. for 5 h, cooling it to 250° C. and keeping it at that temperature for 1 h, and then keeping it at a pressure of 8 MPa for 20 min, to obtain the modified polytetrafluoroethylene sealing ring.
[0059] Example 2
[0060] Preparation of pretreated glass fiber:
[0061] The glass fiber was baked at 380° C. for 2.5 h to obtain pretreated glass fiber.
[0062] Preparation of modified graphite:
[0063] The anti-aging solution includes the following components in parts by weight: 16 parts of sodium tetraborate, 13 parts of copper chloride, 7 parts of chlorogenic acid, 8 parts of ethanol and 55 parts of water;
[0064] First, the graphite is calcined at 340°C for 2.5 hours and then naturally cooled to room temperature to obtain solid A. The solid A with a mass ratio of 1:2 is mixed evenly with an intercalation agent solution, and the mixture is impregnated for 2.5 hours. The solid B is obtained after filtering and washing with water. The solid B with a mass ratio of 1:1.6 and an anti-aging solution are mixed evenly, and the mixture is impregnated for 3 hours. The mixture is dried at 100°C to obtain the modified graphite.
[0065] Preparation of modified polytetrafluoroethylene sealing ring:
[0066] The intercalant solution includes the following components in parts by weight: 13 parts of sulfuric acid, 2 parts of sodium dodecyl sulfate, and 5 parts of phosphoric acid;
[0067] S1. According to weight, 78 parts of polytetrafluoroethylene, 13 parts of pretreated glass fiber, 19 parts of rubber-plastic alloy rubber, 6 parts of polystyrene, 4 parts of modified graphite, 4 parts of carbon powder, and 8 parts of reinforcing agent are added into a pulverizer for mixing and pulverizing to obtain a mixture A, wherein the reinforcing agent is aramid fiber and cerium oxide in a mass ratio of 5:3;
[0068] S2, after passing the mixture A through a 200-mesh sieve, put it into a mixing device, and then add 4 parts of KH550 and continue stirring. The speed of the stirring rod of the mixing device is 1000r / min. After stirring for 20 minutes, the mixture B is obtained;
[0069] S3, heating the mixed material B to 210°C, and after it is completely melted, cold pressing is performed at a pressure of 48 MPa to obtain a raw material blank after 30 minutes;
[0070] S4, calcining the raw material blank at 380° C. for 6 h, cooling it to 260° C. and keeping it at that temperature for 1.5 h, and then keeping it at a pressure of 11 MPa for 25 min, to obtain the modified polytetrafluoroethylene sealing ring.
[0071] Example 3
[0072] Preparation of pretreated glass fiber:
[0073] The glass fiber was baked at 400°C for 3 hours to obtain pretreated glass fiber.
[0074] Preparation of modified graphite:
[0075] The anti-aging solution includes the following components in parts by weight: 20 parts of sodium tetraborate, 15 parts of copper chloride, 10 parts of chlorogenic acid, 10 parts of ethanol and 65 parts of water;
[0076] First, the graphite is calcined at 360°C for 3 hours and then naturally cooled to room temperature to obtain solid A. The solid A with a mass ratio of 1:3 is mixed evenly with an intercalation agent solution, impregnated for 3 hours, filtered and washed with water to obtain solid B. The solid B with a mass ratio of 1:2 is mixed evenly with an anti-aging solution, impregnated for 4 hours, and dried at 105°C to obtain the modified graphite.
[0077] Preparation of modified polytetrafluoroethylene sealing ring:
[0078] The intercalant solution includes the following components in parts by weight: 15 parts of sulfuric acid, 3 parts of sodium dodecyl sulfate, and 6 parts of phosphoric acid;
[0079] S1. Add 85 parts of polytetrafluoroethylene, 15 parts of pretreated glass fiber, 25 parts of rubber-plastic alloy rubber, 9 parts of polystyrene, 5 parts of modified graphite, 5 parts of carbon powder, and 10 parts of reinforcing agent into a pulverizer for mixing and pulverizing to obtain a mixture A, wherein the reinforcing agent is aramid fiber and cerium oxide in a mass ratio of 8:4;
[0080] S2, after passing the mixture A through a 200-mesh sieve, put it into a mixing device, and then add 5 parts of KH550 and continue stirring. The speed of the stirring rod of the mixing device is 1300r / min. After stirring for 25 minutes, the mixture B is obtained;
[0081] S3, heating the mixed material B to 230°C, and after it is completely melted, cold pressing is performed at a pressure of 55 MPa to obtain a raw material blank after 35 minutes;
[0082] S4, calcining the raw material blank at 400° C. for 7 hours, cooling it to 280° C. and keeping it at that temperature for 2 hours, and then keeping it at a pressure of 14 MPa for 30 minutes, to obtain the modified polytetrafluoroethylene sealing ring.
[0083] Comparative Example 1
[0084] The difference between Comparative Example 1 and Example 1 is that the graphite in Comparative Example 1 is not modified, and the other operations are the same.
[0085] Comparative Example 2
[0086] The difference between Comparative Example 2 and Example 1 is that the rubber-plastic alloy rubber is not added in Comparative Example 2, and the other operations are the same.
[0087] Performance Test:
[0088] 1. Hardness test: the test process is carried out in accordance with GB / T2411-2008 "Determination of indentation hardness (Shore hardness) of plastics and hard rubber using a hardness tester", using the Oupu OU2700A Shore hardness tester;
[0089] 2. Wear resistance: According to GB / T3960-2016, the load is 200N, the linear speed is 0.43m / s, the friction pair is GCr15 bearing steel, the wear sample size is 30mm×7mm×4mm, dry friction, the friction time is 60min, the test results are shown in Table 1:
[0090] Table 1
[0091]
[0092] 3. The tensile strength and elongation were tested according to GB / T1040.3-2006. The sealing rings obtained in Examples 1-3 and Comparative Examples 1-2 were heat aged at 280°C for 2000h. The tensile strength of the plastic rods after 2000h heat aging was tested. The test results are shown in Table 2:
[0093] Table 2
[0094]
[0095] According to Table 2, after 2000 hours of heat aging, the tensile strength of Examples 1-3 decreases less, so the polytetrafluoroethylene sealing rings prepared in the examples have better aging resistance.
[0096] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A modified polytetrafluoroethylene sealing ring, characterized in that: The invention comprises the following raw materials in parts by weight: 70 to 85 parts of polytetrafluoroethylene, 10 to 15 parts of pretreated glass fiber, 15 to 25 parts of rubber-plastic alloy rubber, 5 to 9 parts of polystyrene, 3 to 5 parts of modified graphite, 3 to 5 parts of wear-resistant agent, 5 to 10 parts of reinforcing agent, and 3 to 5 parts of silane coupling agent; The specific preparation process of the pretreated glass fiber is to bake the glass fiber at 350-400° C. for 2-3 hours to obtain the pretreated glass fiber.
2. The modified polytetrafluoroethylene sealing ring according to claim 1, characterized in that: The preparation process of the modified graphite is as follows: First, the graphite is calcined at high temperature and then naturally cooled to room temperature to obtain solid A, the solid A with a mass ratio of 1: (1.5-3) and the intercalation agent solution are mixed evenly, impregnated for 2-3 hours, filtered and washed with water to obtain solid B; the solid B with a mass ratio of 1: (1-2) and the anti-aging solution are mixed evenly, impregnated for 2-4 hours, and dried at 95-105° C. to obtain the modified graphite; The anti-aging solution comprises the following components in parts by weight: 10 to 20 parts of sodium tetraborate, 10 to 15 parts of copper chloride, 5 to 10 parts of chlorogenic acid, 5 to 10 parts of ethanol and 40 to 65 parts of water.
3. The modified polytetrafluoroethylene sealing ring according to claim 1, characterized in that: The wear-resistant agent is one or more of carbon powder, carbon fiber, copper powder and molybdenum disulfide.
4. The modified polytetrafluoroethylene sealing ring according to claim 1, characterized in that: The silane coupling agent is one or more of KH550, KH560 and KH570.
5. The modified polytetrafluoroethylene sealing ring according to claim 1, characterized in that: The reinforcing agent is aramid fiber and cerium oxide in a mass ratio of (4-8):(2-4).
6. The modified polytetrafluoroethylene sealing ring according to claim 2, characterized in that: The intercalant solution comprises the following components in parts by weight: 10 to 15 parts of sulfuric acid, 1 to 3 parts of sodium dodecyl sulfate, and 4 to 6 parts of phosphoric acid.
7. The modified polytetrafluoroethylene sealing ring according to claim 2, characterized in that: The temperature of the graphite during high temperature calcination is 300-360° C. and the time is 2-3 hours.
8. A method for preparing a modified polytetrafluoroethylene sealing ring according to any one of claims 1 to 7, characterized in that: The preparation process includes the following: S1, adding polytetrafluoroethylene, pretreated glass fiber, rubber-plastic alloy rubber, polystyrene, modified graphite, wear-resistant agent, and reinforcing agent into a pulverizer in proportion and mixing and pulverizing to obtain a mixture A; S2, after passing the mixture A through a 200-mesh sieve, put it into a mixing device, add a silane coupling agent and continue stirring, the speed of the stirring rod of the mixing device is 900-1300 r / min, and after stirring for 15-25 minutes, a mixture B is obtained; S3, heating the mixed material B to completely melt and then cold pressing to obtain a raw material blank; S4, calcining the raw material blank at 360-400° C. for 5-7 hours, cooling it to 250-280° C. and keeping it at that temperature for 1-2 hours, and then keeping it at a pressure of 8-14 MPa for 20-30 minutes to obtain the modified polytetrafluoroethylene sealing ring.
9. The method for preparing a modified polytetrafluoroethylene sealing ring according to claim 8, characterized in that: In step S3, the heating temperature is 200-230°C.
10. The method for preparing a modified polytetrafluoroethylene sealing ring according to claim 8, characterized in that: In step S3, during the cold pressing process, the pressure is 40-55 MPa and the time is 25-35 min.